Powder Diffraction of Components Subject to Corrosion in Fuse Cutouts with CeramicInsulation - Carvalho, Alex V. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Maciel, Jorge L. B. (Trans Tech Publications Ltd, 2008)
Aiming identification of the components most affected by corrosion under saline environment conditions, we have carried out X-ray diffraction measurements in ceramic and bond materials, all in the powder form. The ceramic is analyzed before and after thermal annealing at 1000 degrees C, showing the same DRX peaks, although better defined after annealing. Identification suggests the presence of Al(6)Si(2)O(13) (Mullite) and SiO(2) (Quartz). Analysis of the junction (bond) material shows similar peaks, but a metallic preponderance is observed. Thermal annealing of the junction is done at much lower temperature, because it melts in the range 135 degrees C-170 degrees C, when a whitish smoke begins to show up along with strong sulfur odor.
Keywords: Fuse cutouts; X-ray diffraction; ceramic; mullite; corrosion